PERANCANGAN UI/UX APLIKASI DAFTAR ACARA SIARAN (DAS) LPP RRI PURWOKERTO MENGGUNAKAN FIGMA - Ananda, Ayu Amarcia; Lia Selvia; Orchid La O.P; Yuni Eka Achyani (STMIK Palangkaraya, 2022)
Radio Republik Indonesia (RRI) is a radio whose broadcasts are intended for the benefit of the nation and state. In carrying out work management, the Public Broadcasting Institution (LPP) RRI Purwokerto can still be said to be not optimal enough, where the preparation and management of reports is still done manually. This causes employees in the planning and broadcaster divisions to experience difficulties when compiling a list of broadcast events. Therefore, the right solution is needed to overcome these problems, namely by designing the User Interface (UI) and User Experience (UX) of the broadcast program list application. The method used in the preparation of this research is design thinking and the use of the Figma application for UI design. The results of this study aim to provide a UI/UX design for the broadcast event list application so that it can help the preparation and management process to be faster, more efficient, and user friendly.